Mengenal Bank â€œSyariahâ€ Lembaga Keuangan untuk Umum - Solihin, Fauzi (Bina Nusantara University, 2001)
The article objective is to compare Syariah banking system to common banking system. It is concluded that Syariah banking system can be alternative banking system to any body who expect profit sharing as the replacement of common interest mechanism.